THE IMPACT OF METACOGNITIVE SKILLS ON STUDENTS’ COGNITIVE DEVELOPMENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the impact of metacognitive skills on students’ cognitive development. According to research, metacognitive strategies — monitoring, evaluating, and regulating one’s thinking process — significantly enhance students’ critical thinking, problem-solving abilities, and academic performance. Developing these skills in primary and secondary education supports students in improving reading comprehension, information retention, and logical thinking. Improving metacognitive skills also increases learners’ motivation and readiness for independent learning. Recent studies shov that assigning tasks based on a metacognitive approach helps students improve self-regulation and the conscious use of learning strategies. As a result, students become more engaged and responsible participants in the educational process. The article emphasizes the importance of integrating metacognitive techniques into everyday learning to support holistic cognitive development in schoolchildren.